2011
DOI: 10.1080/14789949.2010.495991
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of institutional behavioural disturbance and offending in the community among young offenders

Abstract: This study aimed to evaluate the contribution of conduct disorder (CD), substance misuse and attention deficit hyperactivity disorder (ADHD) symptoms to the history of delinquency, current institutional behavioural problems and critical incidents (CI). Fifty-four adolescents in a secure facility were screened for ADHD and CD and completed the Maudsley violence questionnaire, the disruptive behaviour and social problems scale and the self-report delinquency scale. Substance misuse history as well as CI over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
5
21
0
1
Order By: Relevance
“…The Scottish cohort reported that ADHD symptoms predicted aggressive incidents documented in prison records, and this finding remained significant after controlling for antisocial personality traits (S. Young et al, 2009). This supports the findings from other research examining the association between ADHD symptoms and critical incidents in institutionalized youth offenders (S. Young, Gudjonsson, Misch, et al, 2010;S. Young, Misch, Collins, & Gudjonsson, 2011) and personalitydisordered offenders detained in forensic mental health settings (S. Young, Gudjonsson, Ball, & Lam, 2003).…”
Section: Introductionsupporting
confidence: 89%
“…The Scottish cohort reported that ADHD symptoms predicted aggressive incidents documented in prison records, and this finding remained significant after controlling for antisocial personality traits (S. Young et al, 2009). This supports the findings from other research examining the association between ADHD symptoms and critical incidents in institutionalized youth offenders (S. Young, Gudjonsson, Misch, et al, 2010;S. Young, Misch, Collins, & Gudjonsson, 2011) and personalitydisordered offenders detained in forensic mental health settings (S. Young, Gudjonsson, Ball, & Lam, 2003).…”
Section: Introductionsupporting
confidence: 89%
“…One study found that ADHD offenders accounted for eight-times more aggressive incidents than other prisoners, and six-times more incidents when controlling for antisocial personality disorder, suggesting that ADHD contributes to disruptive behavior above and beyond antisocial personality disorder [12]. Similar findings of institutional aggression have been reported among personality disordered patients detained under the Mental Health Act [16] and in youth offending facilities [17]. The phenomenon may be explained by several contributing factors associated with ADHD including impulsive responding, mood instability and low frustration tolerance [18] and a chaotic/disorganized personality style [15].…”
Section: Characteristics Of Adhd Offenderssupporting
confidence: 58%
“…The behavioural difficulties of a child with ADHD are often signals of worsening problems with no intervention made and the presence of CD complicates the picture (Loeber et al, 1992;Johnson et al, 2002;McReynolds et al, 2010;Loeber et al, 2000). Although the association was not statistically significant, other studies have found that ADHD is significantly associated with widespread co-morbidity in childhood, adolescence and in adulthood (Young et al, 2011). Many studies have concluded that the diagnosis of CD and ADHD in adolescents must be taken seriously as children with both conditions are at increased risk of aggression (Loeber et al, 2000) while others have noted the risk of becoming chronic offenders (Vreugdenhil et al, 2004;Young et al, 2011).…”
Section: Discussionmentioning
confidence: 97%